The Role of Part-Time Work Experience in Shaping Start-Up Intentions among Generation Z - Dennis Leonardo Rosli; Yolla Margaretha (Mandalika Institute, 2026)
Generation Z has grown up amid rapid advances in digital technology and demonstrates a strong interest in entrepreneurship, particularly in the form of digital start-ups. However, not all individuals possess the practical readiness required to establish a business. Part-time work experience serves as an informal learning opportunity that fosters discipline, interpersonal skills, and managerial insight. This study aims to examine the effect of part-time work experience on Generation Z's intention to establish a start-up. Although intrinsic motivation and family support are conceptually recognized as potential moderating factors, the empirical analysis in this study focuses on the direct relationship between part-time work experience and start-up intention. A quantitative research approach with a survey design was employed, involving 105 respondents aged 18–26 years who had prior part-time work experience. The data were analyzed using Pearson correlation and simple linear regression with SPSS version 25. The findings indicate that part-time work experience has a positive and significant effect on the intention to establish a start-up (β = 0.468, p < 0.05), explaining 16.6% of the variance in start-up intention (R² = 0.166). These findings suggest that early work experience contributes to Generation Z's entrepreneurial preparedness and confidence, while future research should empirically examine the moderating roles of intrinsic motivation and family support.